Cutaneous mastocytosis in a child with xeroderma pigmentosum: A case report. - Baklan, E.; Duman, N.; Akalın, T.; Karaarslan, I. (European Journal of Pediatric Dermatology, 2024)
Xeroderma pigmentosum is a rare autosomal recessive inherited skin disorder characterized by severe photosensitivity, changes in skin pigmentation, development of malignant tumors at an early age, and sometimes progressive neurological degeneration. Mastocytosis is a rare disease characterized by the increase and accumulation of clonal mast cells in various organs. A two-year-old boy with xeroderma pigmentosum presented with light brown papular lesions, which following skin biopsy were diagnosed as mastocytosis. As far as we know, there is only one adult case in the literature in which xeroderma pigmentosum and mastocytosis occur in the same subject. The current work concerns the coexistence, which has never been previously reported in the literature, of mastocytosis and xeroderma pigmentosum in a child.